Influence of Zinc Substitution on Physicochemical and In-vitro Behaviour of Nanodimensional Hydroxyapatite - Kohli , Suchita; Batra, Uma; Kapoor, Seema (Asian Journal of Engineering and Applied Technology, 2014)
Hydroxyapatite has widely been used as bone substitute due to its good biocompatibility and bioactivity. In the present work, hydroxyapatite was substituted with Zinc (Zn) to improve its bioactivity. The study reports the technique to synthesize nanodimensional pure HA (HA) and Zn substituted HA (ZnHA) powders (with Zn in the range of 2-15 mol%) using sol-gel technique and the influence of Zn on physicochemical and in-vitro behavior of HA. The morphology and size of nanopowders were characterized by transmission electron microscopy (TEM). The BET surface area was evaluated from N2 adsorption isotherms. Structural analysis was investigated by means of x-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR). Invitro study of nanopowders was assessed upto 30 days in simulated body fluid (SBF) maintained at 37 °C. TEM micrographs showed that synthesized HA and ZnHA powders were nanodimensional. HA as well as ZnHA powders (with 2 and 10 mol% Zn) had regular shapes whereas ZnHA powders (with 5 and 15 mol% Zn) had irregular and formed agglomerates. BET surface areas of ZnHA (with 2 and 10 mol% Zn) were higher as compared ZnHA (with 5 and 15 mol% Zn). The XRD and FTIR results revealed that an increase in Zn amount affects the phase composition, crystallization and structural parameters of HA. ZnHA powders exhibited more bioactive behavior than HA.